1999
DOI: 10.1038/6198
|View full text |Cite|
|
Sign up to set email alerts
|

Plants ectopically expressing the ironbinding protein, ferritin, are tolerant to oxidative damage and pathogens

Abstract: Transgenic tobacco plants that synthesize alfalfa ferritin in vegetative tissues--either in its processed form in chloroplasts or in the cytoplasmic nonprocessed form--retained photosynthetic function upon free radical toxicity generated by iron excess or paraquat treatment. Progeny of transgenic plants accumulating ferritin in their leaves exhibited tolerance to necrotic damage caused by viral (tobacco necrosis virus) and fungal (Alternaria alternata, Botrytis cinerea) infections. These transformants exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(112 citation statements)
references
References 44 publications
5
106
0
1
Order By: Relevance
“…A gene encoding a phosphate transporter is suppressed in the plant upon S. meliloti inoculation; this gene is also suppressed upon mycorrhizal colonization (40), indicating shared regulatory steps between the two symbioses. We also identified a homolog of ferritin that is induced in response to S. meliloti (TC39533); ectopic expression of ferritin results in a tolerance to oxidative damage and pathogens (48). Finally, the sugar beet (Beta vulgaris L.) nematode resistance gene is induced in response to nematode feeding (49,50) and is also induced in response to S. meliloti (TC38809).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A gene encoding a phosphate transporter is suppressed in the plant upon S. meliloti inoculation; this gene is also suppressed upon mycorrhizal colonization (40), indicating shared regulatory steps between the two symbioses. We also identified a homolog of ferritin that is induced in response to S. meliloti (TC39533); ectopic expression of ferritin results in a tolerance to oxidative damage and pathogens (48). Finally, the sugar beet (Beta vulgaris L.) nematode resistance gene is induced in response to nematode feeding (49,50) and is also induced in response to S. meliloti (TC38809).…”
Section: Discussionmentioning
confidence: 90%
“…For the sake of simplicity, we assume that each TC represents a single gene and note exceptions to this assumption in the text. To facilitate identification of genes important for the root-based symbiosis, we chose TCs with at least one EST represented in uninoculated root, in S. melilotiinoculated root (24,48, or 72 h postinoculation), or in nodule libraries. In MTGI V.4.0, ESTs from 13 such libraries had been generated.…”
Section: Methodsmentioning
confidence: 99%
“…FTH ferroxidase activity converts reactive iron (Fe 2+ ) into inert iron (Fe 3+ ) that does not partake in the production of free radicals via the Fenton chemistry 95 . This anti-oxidant effect confers tissue damage control and disease tolerance to infection in mammals 87,95 as well as in plants 108 , arguing for the evolutionarily conserved nature of this host defense strategy.…”
Section: Boxmentioning
confidence: 99%
“…Overexpression of ferritin was previously shown to confer resistance to free radical toxicity in tobacco (Nicotiana tabacum) plants (Deak et al, 1999). Interestingly, ferritin, which was the most responsive cDNA clone in the oxidative stress experiment (9-fold induction), contains an electrophile response element with sequence similarity to electrophile response element motifs found in antioxidant response genes, such as glutathione S-transferases and quinone reductase (Tsuji et al, 2000), also identified in this study as ripening regulated and oxidative stress induced.…”
Section: Ripening-regulated Genes In the Receptacle Are Induced By Oxmentioning
confidence: 99%
“…A concentration of 100 mm was selected for the AAPH treatment after performing two independent RNA gel-blot analyses using the strawberry ferritin cDNA as a probe (Fig. 4A), which is known to be induced under stress conditions (Deak et al, 1999). Gene expression in AAPH-treated fruit and those treated with buffer only was compared using the second generation microarrays (experiment V).…”
Section: Ripening-regulated Genes In the Receptacle Are Induced By Oxmentioning
confidence: 99%